Method for the Analysis of Three-Phase Networks Containing Nonlinear Circuit Elements in View of an Efficient Power Flow Computation - Claudiu Tufan (MDPI AG, 2021)
The present paper is devoted to applying the Hănțilă method for solving nonlinear three-phase circuits characterized by different reactance values on the three sequences (positive, negative and zero). Nonlinear elements, which are components of the circuit, are substituted by real voltage or current sources, whose values are an iteratively corrected function of the voltage across or the current through them, respectively. The analysis is carried out in the frequency domain and facilitates an easy evaluation of the power transfer on each harmonic. The paper presents numerical implementations of the method for two case studies. For validation, the results are compared against those obtained using the software LTspice in the time domain. Finally, the power flow on the harmonics and the overall power balance are analyzed.